EFFECTS OF SEDENTARY BEHAVIOR IN PUBLIC HEALTH. (Fiep Bulletin - online, 2016)
Introduction: Staying for extended hours on low energy expenditure activities has been linked to the presence of chronic diseases, health problems and poor health habits by recent epidemiological studies. Objectives: Bibliographical research, systematization and present content analysis in the literature about sedentary behavior associated with health and its determinants in the population. Methods: A review literature research, focused on the survey population data from sedentary behavior and health outcomes. The search for publications was conducted in electronic databases of scientific data, using descriptors theme-related, besides the exploitation of bibliographic references of eligible publications for full-reading. The information has been structured systematically, in order to adjust the content to each predetermined topic and thus establish a linear reasoning and understanding of the theme. For more comprehensive guarantee, it was not carried out the temporal court papers, however was prioritized more recent studies and higher scientific relevance for review. Conclusions: Sedentary behavior appears to be associated with negative health profile rather than any specific chronic disease. Their association with health outcomes appears to occur independent of other lifestyle habits, which represents an important modifiable risk factor in public health promotion.
Keywords: Sedentary behavior; Sedentary lifestyle; Physical inactivity; Public health.